As práticas educativas das educadoras da Escola Municipal de Ensino Infantil e Fundamental 1º de Outubro sob o olhar da educação popular do campo - Souza, Luciane Carneiro de (2019)
The central question of this paper is to investigate whether the educational practices of educators of rural school found not by the Popular Education and the Education field? This is the central question of this paper, which analyses educational practices specifically of the educators of the Municipal School of Child Education and Elementary 1º de Outubro [1st of October], in Dom Marcelo Pinto Carvalheira Rural Settlement in the municipality of Mogeiro – Paraíba. The research takes as theoretical-methodology the Popular education and the Education of the field in the design freiriana of the Praxis from the categories knowledge, dialogue and cultural autonomy. Uses the freiriana as a base perspective, due to the use of dialogue as a means of liberation that creates possibilities of social transformation for the subject overwhelmed. The paths traveled by the methodological approach of qualitative research are based on analysis of semi-structured interviews, observations and documentary research, and its subject, the educators School 1º de Outubro [1st of October] and the pedagogical coordinator of the schools in the municipality of Mogeiro – PB, these, for your time are based on the perspective of Popular education and lists as general objective analysis of the educational practices of the teachers of the School in question, analysis of educational practices the educators of the school concerned, in seeking to identify elements of Popular Education field in the learning process of the students of rural settlement, Dom and specific objectives, defines if the daily life of the subjects observed the field, their identities, experiences and knowledge are being experienced in the educational practices of these educators; identify if the educators have pedagogical knowledge of Popular education and the Education field; and, recognize the practices of educators from school elements and principles of Popular education and education in the field. From the research, noted that the school has specific problems, such as lack of attention from prefecture in relation to the physical structure of the school, lack of school transportation for students and lack of training of field Education for educators In addition to the non-active participation of parents with the school commitment of the students. Finally, understand that, although the educators school examined do not have in-depth knowledge about the field Education and Popular education, use dialogue with learners and the dialogue between the reality of the field and the school content in educational practices used in the classroom, which contributes significantly in the educational development of students.